The Influence of Work Environment and Ambidextrous Leadership on Employee Performance through Career Development - Ardhit Hartono; Junengsih; Nur Dina (Universitas Kadiri, 2026)
Human resources play a strategic role in service-oriented organizations, particularly outsourcing companies whose service sustainability largely depends on employee performance. This study aims to examine the effect of the work environment and ambidextrous leadership on employee performance, with career development positioned as a mediating variable. A supportive work environment, encompassing both physical and psychosocial aspects, contributes to employee comfort, work engagement, and productivity enhancement. Meanwhile, ambidextrous leadership emphasizes a leader’s capability to balance efficiency-driven practices with innovation-oriented behaviors in addressing dynamic organizational challenges. Career development is regarded as a strategic mechanism that aligns individual potential with organizational goals, thereby strengthening employee motivation and performance. This study adopts a conceptual approach through a literature review to construct a framework explaining the relationships among the work environment, ambidextrous leadership, career development, and employee performance. The proposed model highlights the importance of integrating human resource management practices to achieve sustainable employee performance in service-based organizations.